2013
DOI: 10.1016/s2221-1691(13)60161-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of natural honey alone and in combination with curcuma starch against Rhodotorula mucilaginosa in correlation with bioactive compounds and diastase activity

Abstract: The mixture of curcuma starch and honey could lead to the development of new combination antibiotics against Rhodotorula infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Honey contains small amounts of different enzymes, the most important of which are diastase (∝-amylase), invertase (∝-glucosydase), glucose oxidase, catalase and acid phosphatase (White, 1975). They are sensitive to heat and therefore are able to indicate overheating of the product and the degree of conservation (Ahmed et al, 2013). The activity of enzyme in honey also depends on age of the bees, stage of the colony, nectar flow, environmental conditions and the beekeeping practices (Karabournioti and Zervalaki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Honey contains small amounts of different enzymes, the most important of which are diastase (∝-amylase), invertase (∝-glucosydase), glucose oxidase, catalase and acid phosphatase (White, 1975). They are sensitive to heat and therefore are able to indicate overheating of the product and the degree of conservation (Ahmed et al, 2013). The activity of enzyme in honey also depends on age of the bees, stage of the colony, nectar flow, environmental conditions and the beekeeping practices (Karabournioti and Zervalaki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A atividade diastásica corresponde à atividade das enzimas α e β-amilases naturalmente presentes em 1 g de mel, com capacidade de hidrolisar 0,01 g de amido em maltose (dissacarídeo) e maltotriose (trissacarídeo), durante 1 h na temperatura de 40˚C, sendo expressa como o número de diastase nas unidades de Göthe (Ahmed, et al, 2013).…”
Section: Resultsunclassified
“…Limited numbers of studies have examined the activity of Algerian honey against fungi. In brief, Ahmed et al found that the MIC of six varieties of honey against Rhodotorula mucilaginosa ranged between 28% and 36% (v/v) [23] .…”
Section: Discussionmentioning
confidence: 99%